Role of Phytochemicals in Treatment of Aging and Cancer: Focus on Mechanism of FOXO3 Activation - See-Hyoung Park (Antioxidants)
There have been many studies reporting that the regular consumption of fruits and vegetables is associated with reduced risks of cancer and age-related chronic diseases. Recent studies have demonstrated that reducing reactive oxygen species and inflammation by phytochemicals derived from natural sources can extend lifespans in a range of model organisms. Phytochemicals derived from fruits and vegetables have been known to display both preventative and suppressive activities against various types of cancer via in vitro and in vivo research by interfering with cellular processes critical for tumor development. The current challenge lies in creating tailored supplements containing specific phytochemicals for individual needs. Achieving this goal requires a deeper understanding of the molecular mechanisms through which phytochemicals affect human health. In this review, we examine recently (from 2010 to 2024) reported plant extracts and phytochemicals with established anti-aging and anti-cancer effects via the activation of FOXO3 transcriptional factor. Additionally, we provide an overview of the cellular and molecular mechanisms by which these molecules exert their anti-aging and anti-cancer effects in specific model systems. Lastly, we discuss the limitations of the current research approach and outline for potential future directions in this field.